Body image in older breast cancer survivors: A systematic review. Issue 5 (20th February 2020) - Davis, Caitlin; Tami, Perrine; Ramsay, Diane; Melanson, Lydia; MacLean, Leah; Nersesian, Sarah; Ramjeesingh, Ravi
Abstract: Objective: Breast cancer is the most common cancer among women world‐wide. In North America survival rates are >80%, resulting in a large population of survivors. The goal of this review was to systematically explore the literature to identify the status of body image and factors that can impact the body image of older breast cancer survivors. Methods: A systematic review of the literature was conducted and registered with PROSPERO (CRD42019133617). EMBASE and PubMed were searched for articles including terms related to "body image" and "breast cancer." Duplicates were removed and the remaining 322 abstracts were screened. Articles published before 2000, were off‐topic, or those that were non‐primary research articles were excluded. Sixty‐nine remaining full‐length articles were screened for language, gender and location. Seven articles underwent quality assessment of which five passed and were reviewed in depth. The remaining two articles were briefly discussed. Results: The literature review suggests that body image is considered important in older BCS and that body image may impact or be impacted by several factors including age, menopausal status, mental health, treatment modality and exercise. Additionally, themes of dealing with physical changes and the length of time women are impacted following treatment were explored. Conclusion: Our findings highlight that older women may be at an advantage in terms of being post‐menopausal, however concerns surrounding physical and emotional changes affecting body image are indeed present. Future studies on breast cancer survivorship should consider the inclusion of body image as an outcome measure in addition to including individuals representing a wide range of ages.